Perception and Practice of Bangladeshi Adults Towards the Prevention of COVID-19: A Statistical Analysis - Wadood, Md. Abdul; Lee, Lai Lee; Huq, Md. Monimul; Mamun, Asma; Mohd, Suhaili; Hossain, Md. Golam (International Journal of Statistics in Medical Research, 2021)
Background: The coronavirus disease 2019 (COVID-19) has continued to spread across the world with increasing numbers of confirmed cases and deaths. Due to outbreaks of new variants of the virus and limited treatment options, positive perception and good practice of preventive guidelines have remained essential measures for the prevention of the disease and slowing down its transmission. We aimed to study perception towards COVID-19 and the practice of guidelines for preventing the disease among Bangladeshi adults during the early stage of the rapid rise of the outbreak. Methods: Data was collected data from 320 participants. For measuring their level of practice, we asked a general question: “Are you properly following the WHO-recommended guidelines to avoid COVID-19?” The frequency distribution, Chi-square (χ2) test and binary logistic regression model were used in this study. Results: The average risk perception among the participants was 3.05±0.75 (median, 3.00) (95% CI of mean: 2.96-3.13) where the score ranges from 0 (no risk) to 4 (high risk). More than 27% of participants showed high-risk perceptions. Males (p<0.05), high educated (p<0.05), rich (p<0.01), service holders (p<0.05), and younger adults (p<0.05) had higher odds of high-risk perception. More than 71% of participants had a good practice of always following the WHO guidelines to prevent COVID-19 and living locations in urban areas (p<0.01), high education (p<0.01), rich (p<0.01), and joint family (p<0.01) had the most contributions to good practice. Conclusions: The study findings revealed that special attention should be given to rural areas, and individuals of low literacy, education and socioeconomic level to more effectively prevent COVID-19.